Relationship Between Anthropometric Profile with Classification of Bullying in Chilean Vulnerable Schools [Relación Entre Perfil Antropométrico Con la Clasificación de Bullying en Escolares Vulnerables Chilenos] - Herrera-Valenzuela, T (Sociedad espanola de dietetica, 2017)
Introduction: The manifestations of bullying among Chilean students are a recurrent theme within educational establishments. Objective: Determine the relationship between the anthropometric profile with the classification of bullying in vulnerable students of a school in the city of Temuco-Chile (SVT). Methods: The research is transversal. The sample included 36 vulnerable subjects (38.9% female) with a mean for age, weight and height of 12.1 years, 60 kilos and 1.56 meters, respectively. The variables studied corresponded to the anthropometric profile (body composition, somatotype and nutritional status) and classification regarding bullying (through the Assessmente Questionnaire on School Violence in infant and Primary). The analyzed were performed using the Pearson test, Spearman s Rho and Pearson s Chi-square, considering α <0.05. Results: The SVT to reach an average 39% of fat mass, 34% of muscle mass, a somatotype of endo-mesomorphic (6.1 - 5.1 - 1.6), body mass index (BMI) of 24.3 kg/m2 and nutritional status of overweight/obesity that reaches 69.4%; while classification around bullying corresponds to 19.5% of observers, 8.3% of aggressors, 22.3% of victims and 49.9% without participation. Conclusion: Although not confirmed the existence of a statistically significant relationship between anthropometric profile and classification of bullying, it was observed an inverse trend between BMI and subjects classified as victims.